Interface misfit of conventionally milled and novel hybrid full-arch implant-supported titanium frameworks - Xue-Xiao Bai; Ping Di; De-Bin Zhu; Peng Li; Ye Lin (BMC, 2024)
Abstract Objective A hybrid manufacturing technique that combines selective laser melting (SLM) and computer numerical control (CNC) has been developed for the fabrication of implant-platform/framework interfaces (PFIs) for mandibular and maxillary full-arch implant-supported titanium frameworks. The aim of this study was to compare the discrepancies in specimens fabricated using the hybrid technique (termed SLM/m hereafter) with those in specimens fabricated by conventional CNC milling. Materials and methods Based on a mandibular four-PFI CAD model and a maxillary six-PFI CAD model, four groups of titanium frameworks (eight per group, totaling 32) were fabricated according to the fabrication technique (SLM/m or milling) and number of PFIs (four or six). The frameworks were scanned by a structured light scanner and aligned with the CAD model in Geomagic Control X. Discrepancy was defined as the difference between the PFIs of the scanned framework and those of the CAD model. Discrepancies were measured and evaluated by multilevel analysis using a mixed-effects model (α = 0.05), followed by independent samples t-tests (α = 0.0125). Furthermore, the manufacturing times and raw-material costs were recorded and compared. Results The maximum discrepancy values for the four-PFI and six-PFI hybrid frameworks were 52.2 and 64.3 μm, respectively. Multilevel analysis revealed that the fabrication technique and the number of PFIs had no significant effect on the discrepancy value. However, a significant interaction between the two factors was observed (P = 0.020). The discrepancies for the four-PFI hybrid frameworks were significantly lower than those for the four-PFI milled frameworks (P = 0.001). No significant difference in discrepancies between the six-PFI hybrid frameworks and six-PFI milled frameworks was observed (P = 0.697). Furthermore, the hybrid frameworks required only 11% of the raw materials and 25% of the milling time required for the conventionally milled frameworks. Conclusion SLM/m hybrid frameworks are viable, accurate alternatives to CNC-milled frameworks, with the added benefit of substantial cost reduction.